2019
DOI: 10.1093/jee/toz266
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Commercial Insecticide Formulations Against Different Developmental Stages of Insecticide-Resistant Tropical Bed Bugs (Hemiptera: Cimicidae)

Abstract: This study examined the presence of insecticide resistance in different developmental stages (adults, first instars, and eggs) of the tropical bed bug, Cimex hemipterus (F.) using several insecticide formulations. Adults and first instars of five strains (Queensland, Kuala Lumpur, Bukit Mertajam, Saujana, and Krystal Point) were evaluated using the surface contact method and compared with a susceptible strain (Monheim) of the common bed bug Cimex lectularius L. The insecticide formulations were used at their l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…We also noticed that all the three pyrethroid‐resistant C. hemipterus strains (SEL_MY, PEN2_MY, and KUL_MY) carrying the M918I and L1014F mutations were also resistant to fenitrothion and imidacloprid (Table 2). This finding suggests that multiple resistance mechanisms against various classes of insecticides may exist within each population, which was consistent with previous reports 19,33,51 . To understand this further, we investigated if metabolic enzyme activities also contributed to the observed phenomena.…”
Section: Discussionsupporting
confidence: 89%
“…We also noticed that all the three pyrethroid‐resistant C. hemipterus strains (SEL_MY, PEN2_MY, and KUL_MY) carrying the M918I and L1014F mutations were also resistant to fenitrothion and imidacloprid (Table 2). This finding suggests that multiple resistance mechanisms against various classes of insecticides may exist within each population, which was consistent with previous reports 19,33,51 . To understand this further, we investigated if metabolic enzyme activities also contributed to the observed phenomena.…”
Section: Discussionsupporting
confidence: 89%
“…Cotton and Indy populations exhibited RR 50 for deltamethrin less than 2.0, but the mortality was only 73% and 67%, respectively. Similarly, Leong et al [ 56 ] found that bed bugs treated with Tandem insecticide showed a RR 50 value of 1.4 but the mortality was only 53%. The key mechanisms causing pyrethroid resistance among bed bugs are overexpression of detoxification enzymes and the target site insensitivity ( kdr -type mutation) [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 94%
“…One population (Irvington, Table S1 ) had a RR 50 > 160 after being maintained in the laboratory for approximately 10 yr. Likewise, C. hemipterus exhibited high resistance (RR 50 > 600) to neonicotinoid-pyrethroid mixture insecticides after a 14 yr maintenance without exposure to insecticides [ 56 ]. The bed bug resistance to insecticides may therefore not degrade as rapidly as aforementioned.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical control based on the application of residual insecticides remains the primary choice for managing bed bugs infestations 19 , 21 . Numerous studies have reported insecticide resistance in bed bugs to most major insecticide classes including pyrethroid 24 27 , organophosphate 28 31 , neonicotinoid 32 , carbamate 31 , chlorinated hydrocarbons 33 , 34 , and phenylpyrazole 35 . Several mechanisms have been identified to explain the reduced efficiency of insecticides in bed bugs which include penetration resistance due to enhanced cuticle thickness 36 , metabolic resistance due to enhanced expression of xenobiotic metabolizing enzymes 29 , and reduced target site sensitivity due to mutations that causes binding inefficiency of pyrethroids in the voltage gated sodium channels 24 , 25 , 37 .…”
Section: Introductionmentioning
confidence: 99%